The Efforts to Improve the Self-Confidence of Vocational High School Students using Classical Guidance Services with a Project-Based Learning Model - Afriani, Mita Afriani; Rimayati, Elfi; Muslikah, Muslikah; Baihaqi, Mustika Aslam (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to improve students' self-confidence through the implementation of a project-based learning model in guidance and counseling services. The research uses a Guidance and Counseling Action Research (PTBK) approach, which involves a series of systematic actions to address the issue of low student self-confidence. The study was conducted at SMK Negeri 7 Semarang, involving 36 first-year students who experienced difficulties with self-confidence as research participants. The intervention integrated the project-based learning paradigm into guidance and counseling services. The results showed an increase in students' self-confidence by 76.36% after applying the model. In conclusion, the project-based learning model is effective in enhancing the self-confidence of first-year students at SMK Negeri 7 Semarang. The implication of this study is that integrating project-based learning into guidance and counseling services can be an effective strategy to strengthen students' self-confidence, thereby supporting their academic and social development.